The Acceptability of Moist Noodle with Subtitute Flour Mackerel Fish (Rastrelliger SP) - Ayu Bulan Febry Kurnia; Liean Ntau; Deny Indra Setiawan; Nuryani Nuryani (Sarana Ilmu Indonesia (salnesia), 2022)
Fishery products are abundant in Gorontalo Province, so it is necessary to strive for processing to increase the nutritional value and economic value in the manufacture of noodle products. This study aims to determine the acceptability of wet noodle products that have been substituted with mackerel flour (Rastrelliger sp.). The research method used is pure experiment, the samples used are 3 samples, namely F0 wet noodles without the addition of fish meal, F1 wet noodles with 20 grams of mackerel flour using the pressing method, F2 wet noodles with the addition of 20 grams of mackerel flour without pressing. . Acceptability is measured by the level of preference including color, smell, taste and texture with a hedonic scale. Acceptance test was conducted on 25 well-trained panelists. Data analysis with ANOVA (analysis of variance) diversity test and Wicolxon difference test. The results showed that the organoptic diversity test of wet noodles on the color variable showed that there was no difference in color preference between the three wet noodles. While the variables of aroma, taste, and texture of wet noodles showed differences in the level of preference. The results of the different aroma test are known to have p-value <0.05 for F1 with F0 and F2 with F1. Meanwhile, the panelists' level of preference for the aroma of wet noodles F2 is the same as F0. The results of the taste difference test showed that the p-value <0.05 for F1 with F0 and F2 with F0, while the panelists' preference for the aroma of wet noodles F2 was the same as F1. Texture variable, shows p-value < 0.05 for F1 with F0 less than 0.05. It can be concluded that there is a difference in the preferences of the panelists between the aroma of wet noodles F1 and the aroma of wet noodles F0, the aroma of wet noodles F1 and the aroma of wet noodles F0, there is a difference in the preference of the panelists between the texture of wet noodles F1 and the texture of wet noodles F0, there is no difference in the level of preference of the panelists. on the texture of wet noodles F2 with F0 and F2 with F1.